KONTRIBUSI PROGRAM KEAGAMAAN DALAM MENDUKUNG PENCAPAIAN PENDIDIKAN KARAKTER DI SMAN 7 PURWOREJO - Prawidya PL Lestari (Al Ghazali, 2022)
Abstract Strengthening morals is a very important thing to do as is the importance of moral values ​​as human survival. The existence of religious programs in schools is a means for fostering students' morals. In addition, the achievement of character education in schools must also always need to be improved continuously. Because the future of the nation and state always depends on how the education is implemented. SMAN 7 Purworejo is a public school that has a vision, namely the realization of people who have noble character, achievement, culture, care for the environment and have a global perspective. SMAN 7 Purworejo has goals including making school members religious, both in the school environment and in the community, instilling noble character with exemplary patterns by all school members, making school citizens disciplined, and so on. The purpose of this study is to describe the religious programs that exist in SMAN 7 Purworejo, as well as the contribution of religious programs in supporting the achievement of character education at SMAN 7 Purworejo. This research is a field research, where the author goes directly to the field that will be investigated to find out the factors and problems that exist, with an analytical method in the form of a descriptive method, which describes the data in fact or what it is through the exposure of words, as well as a deductive method. namely by connecting the data with research theory for later analysis. The conclusion of this study is that the program implemented at SMAN 7 Purworejo in the context of achieving character education is divided into two, namely in schools such as tartil classes, kultum, student studies, qiroah, PHBI, and others. Then in the dormitory, such as recitations, reading sholawat al-barpromise, studies of fiqh books, habituation to pray in congregation, and also sunnah fasting. The contribution of religious programs in supporting the achievement of character education at SMAN 7 Purworejo is as a means to realize the vision of SMAN 7 Purworejo itself, namely the realization of people who have noble character, achievement, culture, care for the environment and global insight.